330 ORAL ALKALI IMPROVES INDICES OF INCREASED CARDIOVASCULAR RISK IN CHRONIC KIDNEY DISEASE ASSOCIATED WITH PRIMARY HYPERTENSION. (10th December 2015) - Khanna, A.; Simoni, J.; Wesson, D. E.
Abstract : Subjects with compared to those without chronic kidney disease (CKD) have increased risk for cardiovascular disease (CVD). We tested the hypothesis that oral alkali as Na+ citrate improves indices of CVD risk in primary hypertensives with CKD. Nonsmoking hypertensives with CKD (HTN-CKD, calculated GFR = 35 ± 3 mL/min, n = 15) and without CKD (HTN, calculated GFR = 89 ± 3 mL/min, n = 21) had systolic blood pressure (BP) reduced to similar levels (132 ± 2 and 135 ± 1 mm Hg, respectively) over six months with regimens that included angiotensin-converting enzyme inhibitors. After BP reduction, HTN-CKD had higher serum C-reactive protein (CRP) (13.7 ± 1.9 vs. 8.4 ± 0.9 mg/L, p < .01) and higher urine albumin excretion measured by (mg) albumin-to-(g) creatinine (alb/cr) ratio (71.4 ± 20.7 vs. 9.9 ± 1.5, p < .002) in an a.m. specimen. HTN-CKD subjects with serum total CO2 < 22 mM (n = 9) were prescribed Na+ citrate (1 meq HCO3 equivalent/kg/day) as per current recommendations but the remaining HTN-CKD subjects (n = 6) received no alkali therapy. Systolic BP control was unchanged throughout the additional six months of follow-up for alkali-treated and not-treated HTN-CKD subjects. After six months, serum total CO2 increased in the alkali-treated HTN-CKD subjects (20.2 ± 0.4 to 24.4 ± 0.4 mM, p < .001) but decreased in the untreated HTN-CKD subjects (24.0 ± 0.5 vs. 23.3 ± 0.4 mM, p < .02). Serum CRP (13.0 ± 1.3 to 10.2 ± 0.8 mg/L, p < .02, paired t) and urine alb/cr (91.9 ± 29.8 to 67.4 ± 23.7, p < .007, paired t) decreased in the alkali-treated HTN-CKD subjects but neither CRP (14.7 ± 4.6 to 15.7 ± 4.1 mg/L, p = .14, paired t) nor urine alb/cr (40.8 ± 23.4 to 44.2 ± 20.4, p = .35, paired t) changed in the untreated HTN-CKD subjects. These data show that alkali therapy following BP reduction in primary hypertensives with CKD reduces serum CRP and urine albumin excretion, two indices of increased CVD risk. The data suggest that alkali amelioration of metabolic acidosis in subjects with CKD reduces their increased CVD risk.